Clinicopathological Patterns and Stages of Gynaecological Malignancies at Combined Military Hospital, Dhaka (Journal of Shaheed Suhrawardy Medical College, 2026)
Introduction: Now-a-days a surge in gynaecological malignancies has been observed in both developed as well as developing countries, the exact cause is though unknown. Literature shows that every region has disparities in the frequency of commonly occurring cancers.Objective: The objective of this study was to assess frequency, histopathological pattern, stage of various gynaecological malignancies presenting to tertiary care hospital of Bangladesh.Methods: A retrospective hospital-based study was conducted in CMH, Dhaka of Bangladesh from July 2021 to June 2024 for total 3 years.Results: There were 208 patients diagnosed with gynaecological malignancy during the study period. According to the study result, Cervical carcinoma (44.71%) was the most frequently occurring female genital malignancy followed by Ovarian cancer (34.61%) and Endometrial carcinoma (12.5%). Gestational trophoblastic diseases were found in 4.08% cases and  Vulvovaginal cancers were found in total 3.42% cases. 86.02% cases of cervical cancer were SCC and 83.33% of ovarian cancer were epithelial origin. Maximum number of patients belonged to 51-60 years group (34.13%). Cervical cancer had peak incidence at 51-60 years age range compared to patients with ovarian cancer and uterine cancers peaked at age 61-70 years, where GTN peaked at age 31-40 years. Highest proportion of cervical cancer was stage 2 and endometrial cancer was stage 1, while the highest proportion of ovarian cancer was stage 3.Conclusion: Cervical cancer was commonest gynecological malignancy followed by ovarian and then uterine cancer. Late presentation with advanced stage was seen in majority of all cancers.J Shaheed Suhrawardy Med Coll 2024; 16(2): 2-6